1970
DOI: 10.1002/cne.901390106
|View full text |Cite
|
Sign up to set email alerts
|

The lateral cervical nucleus of cat, dog and man

Abstract: This nucleus was identified in four cats, four dogs and nine human spinal cords, but was not identifiable in seven other human specimens. In all three species the nucleus extends rostrally into the lower third of the medulla. Cell measurements of the perikarya yielded a mean diameter of 34.1 p in the dog, 26.7 / . L in the cat, and 15.7 it in man, Nuclear diameters as well as the nucleus-cytoplasm and volume ratios were determined. The lateral cervical nucleus is considered to be rudimentary in man and was a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…These cells usually have elongated dendrites that form a cylinder in the dorso-ventral axis. However, it is unclear whether the SCT exists in humans, as this tract might be rudimentary in primates (Truex et al 1970).…”
Section: Projection Neuronsmentioning
confidence: 99%
“…These cells usually have elongated dendrites that form a cylinder in the dorso-ventral axis. However, it is unclear whether the SCT exists in humans, as this tract might be rudimentary in primates (Truex et al 1970).…”
Section: Projection Neuronsmentioning
confidence: 99%
“…In addition, the size of LCN neurons was larger in calves than it was in pigs. Since previous studies have demonstrated that the neuronal size of the LCN neurons is not related to the animal body size (Truex et al 1970), we could assume that the bovine LCN is more developed than that of the pig. This is the opposite of the situation found in other nuclei in the bovine compared to the pig (Graïc et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…J ou and Tsai, 1971 ] of the spino-cervico-thalamic system of the Formosan rock-monkey (Macaca cyclopis) has demonstrated a thin, slender nucleus in the dorsolateral white column extending from I he low er portion of the medulla oblongata to the caudal half of the second cervical segment of the spinal cord. This nucleus occupies the same region and has a similar histological appearance to that of the NCL in the cat [Rexed and Brodal, 1951;Rexed and Strom, 1952;Truex et al, 1970): the dog [Kitai, Ha and Morin, 1963; Tin ex …”
mentioning
confidence: 99%